2014
DOI: 10.1038/ncomms5730
|View full text |Cite
|
Sign up to set email alerts
|

Mycobacterium tuberculosis acquires iron by cell-surface sequestration and internalization of human holo-transferrin

Abstract: Mycobacterium tuberculosis (M.tb), which requires iron for survival, acquires this element by synthesizing iron-binding molecules known as siderophores and by recruiting a host iron-transport protein, transferrin, to the phagosome. The siderophores extract iron from transferrin and transport it into the bacterium. Here we describe an additional mechanism for iron acquisition, consisting of an M.tb protein that drives transport of human holo-transferrin into M.tb cells. The pathogenic strain M.tb H37Rv expresse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
82
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 94 publications
(85 citation statements)
references
References 60 publications
2
82
0
1
Order By: Relevance
“…When entering bacterial cells by means of siderophores, Fe 3ϩ is reduced to Fe 2ϩ for incorporation into mycobacterial iron-containing proteins, including iron storage proteins like bacterioferritin (1). Other known mycobacterial iron uptake mechanisms include heme uptake (8,9), internalization of holo-transferrin (10), and low-affinity iron uptake through outer membrane porins (11). Guinea pigs and mice infected by M. tuberculosis strains deficient in siderophore synthesis or transport across the cell membrane show a significant reduction in bacterial burden compared to animals infected by wild-type (WT) M. tuberculosis (12,13), demonstrating the need for iron in mycobacterial virulence.…”
mentioning
confidence: 99%
“…When entering bacterial cells by means of siderophores, Fe 3ϩ is reduced to Fe 2ϩ for incorporation into mycobacterial iron-containing proteins, including iron storage proteins like bacterioferritin (1). Other known mycobacterial iron uptake mechanisms include heme uptake (8,9), internalization of holo-transferrin (10), and low-affinity iron uptake through outer membrane porins (11). Guinea pigs and mice infected by M. tuberculosis strains deficient in siderophore synthesis or transport across the cell membrane show a significant reduction in bacterial burden compared to animals infected by wild-type (WT) M. tuberculosis (12,13), demonstrating the need for iron in mycobacterial virulence.…”
mentioning
confidence: 99%
“…Our lab and others have shown that M. tuberculosis replicating in human macrophages can acquire Fe bound to transferrin or lactoferrin and from exogenous sources (13)(14)(15)(16). Fe is an important component of enzymes involved in critical cellular functions such as DNA synthesis (17), general metabolism, and oxidative stress resistance.…”
mentioning
confidence: 99%
“…Boradia et al [40] reported the over-expression of GAPDH, correlated with a corresponding increase in transferrin binding and iron uptake in mycobacteria. Spot 11 is probable CoAtransferase alpha subunit (Rv3551).…”
Section: Accepted Manuscriptmentioning
confidence: 98%